Essentials of neuro- ophthalmology - Mukherjee, PK (Panamá : Jaypee Brothers Medical Publishers, 2010)
The purpose of this book is to make the reader at ease and confident in dealing with neuro-ophthalmic cases. Emphasis has been given to even those clinical features that seem to be too trivial but have profound significance, for instance pupillary reaction, colour sense, diminished brightness, fleeting diplopia, field changes etc.
1. Symptomatology in neuro-ophthalmic didorders 2. Applied anatomy of the cranial nerves of neuro-ophthalmic 3. Disorders of the visual pathway 4. Pupillary Change in neuro-opthalmic 5. Neuro-ophthalmic disorders of the lids y otros
Título en inglés
Keywords: OFTALMOLOGÍA; ENFERMEDADES OCULARES